Detection of Counterfeit Telecommunication Products using Luhn Checksum Algorithm and an Adapted IMEI Authentication Method - Amusa, Morufu; Bamidele, Oluwade (2020)
The problem of counterfeiting of telecommunication products is not confined only to the end products. It extends to accessories and components such as batteries, hardware, switches, adapters, USBs etc. Counterfeiting is real and it may be regarded as a social security. That is, a platform for identifying adulterated products and promoting anticounterfeit activities is very important. Though a sole and absolute protection against counterfeiting is rare, there is need for deployment of a combination of technologies which will assist to mitigate the magnitude of this phenomenon significantly. This paper presents two authentication methods for detecting counterfeit and substandard telecommunication devices/products via the International Mobile Equipment Identity (IMEI) number. The first authentication method is the Luhn checksum algorithm, otherwise called Luhn formula or mod 10 algorithm. This algorithm is generally used to validate identification numbers such as IMEI, debit/credit card numbers, social security numbers, national identification numbers etc. The second method is an authentication method earlier developed for counterfeit drugs, which is here adapted to counterfeit telecommunication products via IMEI. IMEI is a unique number embedded in a telecommunication device which serves as identity for the device.